Model reduction and frequency residuals for a robust estimation of nonlinearities in subspace identification. (1st September 2017) - De Filippis, G.; Noël, J.P.; Kerschen, G.; Soria, L.; Stephan, C.
Highlights: The FNSI method is improved by a strategy for removing spurious poles. Frequency residuals are even more introduced in the estimation procedure. Spurious pole removal is obtained operating on the identified state-space matrices. The effectiveness has been proved by using data from a complete aircraft structure. The nonlinear identification moves from both numerical and experimental data. Abstract: The introduction of the frequency-domain nonlinear subspace identification (FNSI) method in 2013 constitutes one in a series of recent attempts toward developing a realistic, first-generation framework applicable to complex structures. If this method showed promising capabilities when applied to academic structures, it is still confronted with a number of limitations which needs to be addressed. In particular, the removal of nonphysical poles in the identified nonlinear models is a distinct challenge. In the present paper, it is proposed as a first contribution to operate directly on the identified state-space matrices to carry out spurious pole removal. A modal-space decomposition of the state and output matrices is examined to discriminate genuine from numerical poles, prior to estimating the extended input and feedthrough matrices. The final state-space model thus contains physical information only and naturally leads to nonlinear coefficients free of spurious variations. Besides spurious variations due to nonphysical poles, vibration modes lying outside the frequency band of interest may also produce drifts of the nonlinear coefficients. The second contribution of the paper is to include residual terms, accounting for the existence of these modes. The proposed improved FNSI methodology is validated numerically and experimentally using a full-scale structure, the Morane-Saulnier Paris aircraft.